Optimalisasi Manajemen Mutu Pendidikan Islam melalui Pendekatan Total Quality Management (TQM) - Ismail Mustaqim; Asep Nuhdi; Agus Suryana (Pascasarjana IAI Nasional Laa Roiba Bogor, 2026)
Islamic education faces challenges in the globalization era, such as low accreditation, weak graduate competitiveness, irrelevant curriculum, and rigid institutional management. This study aims to describe the concept of Total Quality Management (TQM) in Islamic education quality management, analyze its relevant principles (customer focus, continuous improvement, involvement of all parties, systemic approach, and data-based decisions), outline its implementation in Islamic universities such as Darussalam Islamic University in Ciamis and PTIQ Institute in Jakarta, identify challenges (limited human resources, resistance to change, infrastructure, and organizational culture), and evaluate strengthening strategies such as the integration of Islamic values, leadership commitment, human resource training, stakeholder collaboration, and digitalization. The research method is a library research with qualitative analysis through content analysis of primary data (books, journals, case studies of TQM and Islamic education) and secondary data (regulations, quality documents). The results of the study indicate that TQM is aligned with Islamic values such as ihsan, istiqamah, shura, and amanah, capable of improving holistic quality (academic, spiritual, character). Implementation resulted in increased accountability and stakeholder satisfaction, despite resource constraints. The strengthening strategy emphasized the synergy of modern managerial and Qur'anic values to achieve superior graduates, both globally and Islamically. Conclusion: TQM is a manifestation of worship in producing a generation of moral and professional quality.